From Awareness to Action: A Conceptual Framework for Participatory Resilience in the Chinese Context - Dong, Qiuyu (International Journal of Humanities and Social Science, 2025)
As climate risks grow increasingly complex and governance systems undergo institutional change, fostering individual-level public engagement has become a critical challenge in risk research. Existing studies often focus on macro-level institutions and community practices, with limited attention to the behavioral mechanisms at the individual level. This study proposes a theoretical framework of participatory resilience that expands the micro-analytic dimension of social resilience theory through the lens of individual behavior change. Drawing on the Social Cognitive Theory and the Theory of Planned Behavior, the paper introduces a five-stage behavioral pathway model comprising cognitive activation, emotional resonance, evaluative judgment, motivational development, and behavioral transformation. By integrating international experiences with bibliometric analysis of both Chinese and English literature, the study identifies gaps in current research-particularly the insufficient attention to individual behavioral transformation and the lack of clearly defined institutional embedding mechanisms in state-led governance environments. The findings contribute to resilience theory by offering a micro-level analytical perspective that links individual cognition and motivation to broader systemic resilience-building efforts.